Development of Salt-Tolerant Soybean Germplasm Screening Criteria and Functional Validation of GmWRKY142 and GmWRKY89 in Arabidopsis - Shixu Sun; Yongbo Yu; Youju Huang; Cuijing Pang; Musen Lin; Fenglei Liu; Hongbing Yang; Yanchong Yu (Journal of Plant Growth Regulation, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Anti-aging effects of low-molecular-weight polysaccharide PSP-1-1 from steamed Polygonatum sibiricum via gut microbiota modulation - Chen Zhang; Hongru Lin; Congmin Wei; Xue Long; Shuomeng Bai; Haotian Wu; Xinran Li; Zhou Yang; Yihuai Gao; Hongbing Wang (Carbohydrate Polymers, 2026)

HDAC5 mediates the regulation of muscle-derived interleukin 6 on the differentiation of porcine intramuscular pre-adipocytes - Weimin Lin; Hongbing Song; Chongfan Du; Jing Wang; Xiaohan Zhang; Chu Yang; Tianfang Xiao; Ruiyi Lin (Domestic Animal Endocrinology, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

Co(salen)-based hyper-crosslinked porous ionic polymer as heterogeneous synergistic catalyst for the cycloaddition of CO2 with epoxides - Yaju Chen; Yongjian Qiu; Zhitong Wang; Xiaoxue Zhou; Haowen Chen; Lin Lei; Yating Wang; Hongbing Ji (Fuel, 2026)

Physiological and transcriptome analyses in Yulania stellata under flooding stress - Lin Xu; Lianlian Pan; Kang Ye; Jun Qin; Yonghong Hu; Chenbing Guo; Duorun Wu; Hongbing Wang (New Zealand Journal of Botany, 2025)

Pollution characteristics and influencing factors of rural greywater: A field investigation across China - Hao Wang; Xuejiao Han; Xingzhou Lin; Yao Chen; Bin Hong; Qijia Cai; Wenli Zheng; Jianying Chao; Licai Hu; Jiping Xiao; Junneng Wang; Hongbing Zhao; et al. (Journal of Environmental Management, 2025)

Sonochemical synthesis of bilayer V2O5 for zinc-ion batteries - Haiyuan Lin; Jiangfeng Gong; Yonghao Guan; Zhibin Shao; Chunmei Tang; Hongbing Yao; Wenyi He; Guangchao Du (Chemical Engineering Journal, 2025)

An interpretable machine learning framework for optimizing chemical oxidative remediation of organic pollutants in soils - Yuanshuo Zhang; Haojia Chen; Yudong Cao; Xuxin Liang; Hongbing Ji; Kunsen Lin; Yan Yang (Journal of Environmental Chemical Engineering, 2025)

Soybean GmWRKY44 transcription factor activates SOC1 and LFY to promote flowering in Arabidopsis thaliana - Youju Huang; Cuijing Pang; Yongbo Yu; Shixu Sun; Musen Lin; Hongbing Yang; Yanchong Yu (Plant Cell Reports, 2025)

Integrative analysis of copper dysregulation and cuproptosis in postnatal hematopoiesis - Liyun Chen; Qian Wu; Chaohui Lin; Zijun Song; Yunxing Su; Chaodong Ge; Xue Wang; Hongbing Luo; Rong Wang; Yanfang Wang; Junxia Min; Fudi Wang (Science Bulletin, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Retearing of type B blind cystic aortic dissection: computational fluid dynamics analysis - Hongbing Chen; Yujing Huang; Tong Su; Qi Wang; Minzhu Zhao; Shangyu Zhang; Ruijiao Lin; Jianbo Li (Physical and Engineering Sciences in Medicine, 2025)

Absorption, transport, blood-brain barrier penetration, and neuroprotection of walnut peptides LR and LPI - Shuguang Wang; Yao Tang; Guowan Su; Lin Zheng; Yongliang Zhuang; Bifen Chen; Hongbing Fan; Mouming Zhao; Jianping Wu (Food Research International, 2025)

Characteristics, source analysis, and risk assessment of organochlorine pesticide contamination in nearshore surface sediments of a tropical tourist island - Hongbing Wang; Lin Zhang; Feng Yang; Li Yan; Cong Lin; Cheng Shen (Frontiers in Marine Science, 2025)
Surface sediment samples were collected from the surrounding waters of the two largest tourist islands in Sanya, China, to compare and evaluate the sources, distribution, and ecological risks of 21 organochlorine pesticides (OCPs). The total concentration of OCPs ranged from 1.35 to 5.0 ng/g. Among the OCPs, ΣDDTs accounted for the largest proportion, followed by ΣHCHs. The concentrations of HCHs and DDTs from the west side of West Island were significantly higher than those from the east side, and fine-grained sediments exhibited a stronger adsorption effect on OCPs. Source analysis indicated that the area experienced new inputs of HCH pollutants, while historical residues of HCHs remained high. Residual OCPs are still widely present in the environment, transported mainly by river runoff, with a smaller portion originating from atmospheric deposition and ship paints. Ecological risk assessment results showed that factors occasionally causing adverse biological effects include Heptachlor epoxide, 4,4'-DDE, ΣDDT, Dieldrin, Endrin, and γ-HCH, while other factors rarely caused negative biological effects. Potential ecological effect evaluations indicated that stations SY03, SY04, SY06, and SY09 were classified as having moderate ecological effect levels, while other stations were classified as having no ecological effects. Strengthened investigation, monitoring, and control of pollutant sources in ecologically impacted areas are necessary. This study fills a data gap for the region and provides an academic foundation for environmental protection and the sustainable development of tourism resources.

Temperature-responsive gating chitosan-based microcapsules for controlled release of urea fertilizers - Nian Xiang; Yuming Lin; Zuzeng Qin; Tongming Su; Xinling Xie; Hongbing Ji (Carbohydrate Polymers, 2025)

Microneedle patch with pure drug tips for delivery of liraglutide: pharmacokinetics in rats and minipigs - Hongbing Lin; Jinbin Liu; Yulin Hou; Zhiyan Yu; Juan Hong; Jianghong Yu; Yu Chen; Jingwen Hu; Dengning Xia (Drug Delivery and Translational Research, 2025)

Octopus-inspired flocculant for oily wastewater decontamination: Hydrophilic-hydrophobic convertibility and auto-separation characters - Wei Chen; Zhihan Zhao; Yuhan Du; Shuohao Ouyang; Mengyi Lin; Fengya Li; Hanwei Tang; Hongbing Luo; Ke Zhang; Huaili Zheng (Journal of Hazardous Materials, 2024)

Spatial distribution characteristics, ecological risk assessment, and source analysis of heavy metal(loid)s in surface sediments of the nearshore area of Qionghai - Junyi Jiang; Miao Fu; Jianying Yang; Yanwei Song; Guowei Fu; Hongbing Wang; Cong Lin; Yang Wang (Frontiers in Marine Science, 2024)
To understand the pollution characteristics and potential sources of heavy metal(loid)s in the nearshore sediments of Qionghai, 93 surface sediment samples were collected from the region. The concentrations of 20 elements, including Fe, Mg, Ca, Ti, Mn, Ba, Cr, Sr, Ni, Cu, Zr, As, Hg, Se, Be, Co, Mo, Cd, Ga, and Pb, were measured. The extent of contamination and ecological risk posed by these heavy metals/metalloids were evaluated using the geo-accumulation index, potential ecological risk index, and Nemerow comprehensive risk index. Additionally, correlation analysis, principal component analysis (PCA), and positive matrix factorization (PMF) were employed to identify the potential sources of these elements in the sediments. The findings reveal the following: (1) The mean concentrations of Fe, Ca, Mg, Ti, Cu, Sr, Zr, Mo, Cd, Pb, Hg, As, and Se exceed the background values for shallow sea sediments in China. Notably, Ca, Ti, Sr, Zr, Mo, Hg, and As exhibit coefficients of variation greater than 51%, indicating significant spatial variability primarily driven by anthropogenic activities. (2) The ecological risk assessment identifies Sr, Hg, and As as the principal pollutants and key potential ecological risk factors in the study area, necessitating prioritization in subsequent monitoring efforts. (3) Correlation and source analysis suggest that As and Mn primarily originate from agricultural activities, Sr, Ca, and Mg from aquaculture, Zr, Ti, Mo, Se, Pb, Be, Co, Cu, Ga, Ni, Fe, and Cd from natural sources, and Hg, Ba, and Cr from transportation sources. Additionally, this study identified Sr, Hg, and As as the primary pollutants in the Qionghai nearshore area, with sources predominantly linked to agriculture, aquaculture, and traffic. Regular monitoring will help track the effectiveness of implemented control measures and provide data for ongoing risk assessments, ensuring the protection and sustainability of the marine environment.

Synthesis of hydrothermal carbonation carbon with tunable photocatalytic performance for trimethoprim degradation using an ethanol-water co-solvent strategy: Influence of ethanol concentration - Jiashuai Hu; Jie Chen; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; Wei Chen; et al. (Journal of Cleaner Production, 2024)

Pt/MgO catalysts intrinsically promoted by fast moving bed pyrolysis for hydrogenation properties - Hao Zhang; Hongfei Lin; Ziyue Wang; Liyang Liu; Hao Liu; Xiaohui He; Hongbing Ji (Chemical Engineering Journal, 2024)

Characteristics, sources analysis, and risk assessment of polycyclic aromatic hydrocarbon contamination in surface sediments surrounding tourist island - Hongbing Wang; Jianwei Dong; Junqiao Long; Junyi Jiang; Cong Lin (Marine Pollution Bulletin, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Perovskite intermediate phase FAPbBr3·DMSO assisted in-situ growth of FAPbBr3 polycrystalline wafer for X-ray detection and imaging - Dan Liu; Wei Jiang; Siyin Dong; Haipeng Di; Haibin Li; Zhenning Xing; Hongbing Wang; Jiwei Ren; Xiaojia Zheng; Lin Lei; Yiying Zhao (Chemical Engineering Journal, 2024)

Amphichdiral enhancement on singlet oxygen generation and stable thallium immobilization using iron-driven copper oxide - Zhujun Liu; Xinning Dai; Jun He; Mengyi Lin; Hongbing Luo; Liangqian Fan; Ke Zhang; Dandan Ma; Jun Wang; Wei Chen (Journal of Environmental Management, 2024)

Ovalbumin promotes innate immune response of Caenorhabditis elegans through DAF-16 and SKN-1 pathways in insulin/IGF-1 signaling - Haibing Pei; Zhiyin Lin; Kexin Yao; Yeqing Luo; Ping Tong; Hongbing Chen; Yong Wu; Zhihua Wu; Jinyan Gao (Journal of Physiology and Biochemistry, 2024)

Machine learning models for predicting thermal desorption remediation of soils contaminated with polycyclic aromatic hydrocarbons - Haojia Chen; Yudong Cao; Wei Qin; Kunsen Lin; Yan Yang; Changqing Liu; Hongbing Ji (Science of The Total Environment, 2024)

Ultrasensitive and highly stretchable bilayer strain sensor based on bandage-assisted woven fabric with reduced graphene oxide and liquid metal - Yankun Lin; Qing Yin; Hongbing Jia; Qingmin Ji; Jingyi Wang (Chemical Engineering Journal, 2024)

Efficient hydrogen recovery from wastewater treatment by piezo-photocatalytic heterostructure - Xinning Dai; Zhujun Liu; Zhihan Zhao; Jun Wang; Hongbing Luo; Lin Cheng; Wei Chen (Journal of Cleaner Production, 2024)

Cellulose nanofibers embedded chitosan/tannin hydrogel with high antibacterial activity and hemostatic ability for drug-resistant bacterial infected wound healing - Dangwei Li; Xiangyang Dong; Xia Liu; Heng Lin; Di Yang; Xiaowen Shi; Chaoji Chen; Fenghua Tao; Linbin Jiang; Hongbing Deng (Carbohydrate Polymers, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

Visible light-driven Cl-g-C3N4 activated peroxydisulfate process for TMP efficient degradation in a wide pH range - Jie Chen; Jiashuai Hu; Yuanmao Lin; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; et al. (Journal of Water Process Engineering, 2024)

Exploring the nonlinear association between agri-environmental regulation and green growth: The mediating effect of agricultural production methods - Hongbing Zhu; Lihua Yang; Changxin Xu; Tianbo Fu; Jianting Lin (Journal of Cleaner Production, 2024)

Self-assembly kieselguhr-based ZSM-5 for catalytic pyrolysis of mask waste to produce high value-added aromatics - Yufei Gu; Hucheng Ge; Yuke Liu; Qi Wei; Tianhua Gao; Hengshuo Gu; Hongbing Fu; Fuwei Li; Hongfei Lin; Lei Miao; Zhixia Li (Fuel, 2024)

Novel perspective on the regulation of food allergy by probiotic: The potential of its structural components - Huming Shao; Fangfang Min; Meijia Huang; Zhongliang Wang; Tianliang Bai; Min Lin; Xin Li; Hongbing Chen (Critical Reviews in Food Science and Nutrition, 2024)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Image-based estimation of crown volume of individual street trees by plane calculation of angle disparity - Chenbing Guo; Yonghong Hu; Jun Qin; Lin Xu; Meihan Chu; Hongbing Wang (Urban Forestry & Urban Greening, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Yeast biomass ornamented macro-hierarchical chitin nanofiber aerogel for enhanced adsorption of cadmium(II) ions - Iqra Shahzadi; Yang Wu; Heng Lin; Jing Huang; Ze Zhao; Chaoji Chen; Xiaowen Shi; Hongbing Deng (Journal of Hazardous Materials, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Measuring segregation in fluidized bed with magnetizable and nonmagnetizable particles based on magnetic permeability - Quanhong Zhu; Qiang Zhang; Peiyi Yang; Hengjun Gai; Mengqi Lin; Hongbing Song; Meng Xiao; Tingting Huang (Fuel, 2023)

Overview of the main biological mechanisms linked to changes in periodontal ligament stem cells and the inflammatory microenvironment - Xuetao Zhao; Hongbing Lin; Tong Ding; Yawei Wang; Na Liu; Yuqin Shen (Journal of Zhejiang University-SCIENCE B, 2023)

Novel Al-doped UiO-66-NH2 nanoadsorbent with excellent adsorption performance for tetracycline: Adsorption behavior, mechanism, and application potential - Liangqian Fan; Jiaxin Miao; Xianda Wang; Jie Cai; Jiawei Lin; Fenghui Chen; Wei Chen; Hongbing Luo; Lin Cheng; Xiaochan An; Xiaoxiao Zhang; Ke Zhang; et al. (Journal of Environmental Chemical Engineering, 2023)

Dual-dense gas-solid circulating fluidized bed reactor - Hengjun Gai; Peiyi Yang; Qiang Zhang; Mengqi Lin; Hongbing Song; Meng Xiao; Tingting Huang; Quanhong Zhu (Fuel, 2023)

Catalytic co-cracking of biomass and waste plastics with sawdust mediated ZSM-5 synthesized via activating gel process - Fuwei Li; Xiaofeng Wang; Hengshuo Gu; Hongbing Fu; Asad Ali; Hongfei Lin; Zhixia Li (Fuel, 2023)

Changes in plant anthocyanin levels in response to abiotic stresses: a meta-analysis - Wenjie Yan; Juanjuan Li; Xinyue Lin; Lina Wang; Xiaoxiao Yang; Xiangyu Xia; Yuxin Zhang; Shaoyu Yang; Hongbing Li; Xiping Deng; Qingbo Ke (Plant Biotechnology Reports, 2022)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Clinical characteristics of 24 asymptomatic infections with COVID-19 screened among close contacts in Nanjing, China - Zhiliang Hu; Ci Song; Chuanjun Xu; Guangfu Jin; Yaling Chen; Xin Xu; Hongxia Ma; Wei Chen; Yuan Lin; Yishan Zheng; Jianming Wang; Zhibin Hu; et al. (Science China Life Sciences, 2020)

Characterization and Genome Analysis of a Novel Alteromonas Phage JH01 Isolated from the Qingdao Coast of China - Dongxu Wang; Yong Jiang; Shicong Xiao; Min Wang; Qian Liu; Liyang Huang; Chenglong Xue; Qi Wang; Tongtong Lin; Hongbing Shao; Andrew McMinn (Current Microbiology, 2019)

Adsorption Removal of Cr(VI) with Activated Carbon Prepared by Co-pyrolysis of Rice Straw and Sewage Sludge with ZnCl2 Activation - Liangqian Fan; Wenxin Wan; Xianda Wang; Jie Cai; Fenghui Chen; Wei Chen; Lin Ji; Hongbing Luo; Lin Cheng (Water, Air, & Soil Pollution, 2019)

The association study of nonsyndromic cleft lip with or without cleft palate identified risk variants of the $$\varvec{GLI3}$$ G L I 3 gene in a Chinese population - Yirui Wang; Yimin Sun; Yongqing Huang; Yongchu Pan; Bing Shi; Jian Ma; Lan Ma; Feifei Lan; Yuxi Zhou; Jiayu Shi; Jinfang Zhu; Hongbing Jiang; et al. (Journal of Genetics, 2017)

A cis-eQTL genetic variant of the cancer–testis gene CCDC116 is associated with risk of multiple cancers - Na Qin; Cheng Wang; Qun Lu; Tongtong Huang; Meng Zhu; Lihua Wang; Fei Yu; Mingtao Huang; Yue Jiang; Juncheng Dai; Hongxia Ma; Guangfu Jin; et al. (Human Genetics, 2017)

Characterization and Genome Sequence of Marine Alteromonas gracilis Phage PB15 Isolated from the Yellow Sea, China - Yu Gao; Qian Liu; Min Wang; Guihua Zhao; Yong Jiang; Gill Malin; Zheng Gong; Xue Meng; Zhaoyang Liu; Tongtong Lin; Yutong Li; Hongbing Shao (Current Microbiology, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Genetic variants at 4q21, 4q23 and 12q24 are associated with esophageal squamous cell carcinoma risk in a Chinese population - Yong Gao; Yisha He; Jing Xu; Lin Xu; Jiangbo Du; Chen Zhu; Haiyong Gu; Hongxia Ma; Zhibin Hu; Guangfu Jin; Xiaofei Chen; Hongbing Shen (Human Genetics, 2013)

CFD and digital particle tracking to assess flow characteristics in the labyrinth flow path of a drip irrigation emitter - Yunkai Li; Peiling Yang; Tingwu Xu; Shumei Ren; Xiongcai Lin; Runjie Wei; Hongbing Xu (Irrigation Science, 2008)